Jogos eletrônicos nas aulas de Educação Física no ensino fundamental: visão docente - Jerônymo, Wellington Hencklein (Universidade Federal de São Carlos, 2022)
Inside schools, it is possible to observe an increasing number of cell phones and technological devices in the hands of students, which a few years ago was seen as something negative. However, currently, it is understood that it is necessary to adapt national and regional and teachers to introduce such tools in the teaching and learning process, supported by changes in the Common Curricular Base (BNCC) of 2017, where games are discussed. electronics in Physical Education. Taking this “new” content as a starting point, presented for the 6th and 7th grades of elementary school, final years, the aim of this research is to analyze how Physical Education teachers in elementary school, from public schools in São Carlos, in the countryside from the state of São Paulo, work or envisage working with electronic games in their classes, what are their previous knowledge and experiences on the subject, in addition to their perspectives on being present at the BNCC. Data were collected through a mixed questionnaire, with open and closed questions, electronically (google forms). The collected data were analyzed and organized into four different categories, namely: (1) Perception about electronic games, where it is discussed what the subjects understand by “electronic games”; (2) View of the students – according to the teachers – about electronic games, which seeks to understand the perception of teachers about the relationship between their students and electronic games; (3) Electronic games in the school environment, dealing with their use for pedagogical purposes in the classroom; (4) Training of teachers regarding electronic games and pedagogical possibilities, exploring the knowledge and confidence that subjects have to use electronic games as a learning tool in their classes. The results point to teachers' difficulties in proposing content outside the materials made available by the state, linked to lack of knowledge about the topic, especially its pedagogical potential. Based on the teachers' responses and going beyond the curriculum proposed by the state, we suggest elements for a possible didactic unit that addresses the history of electronic games up to contemporary e-sports so that, with the help of students, an experience of these games can be carried out in school environment.
Electronic games in physical education classes in elementary education: teacher's vision
Keywords: Jogos eletrônicos; Educação física escolar; Docentes; BNCC; Electronic games; Physical education; Teachers; CIENCIAS HUMANAS::EDUCACAO::CURRICULO